1969
DOI: 10.1677/joe.0.0450531
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Androgen Receptor in the Cytoplasm of Rat Prostate

Abstract: SUMMARY A thermolabile protein with the properties of a steroid 'receptor' was identified in the cytoplasmic or 105,000 g supernatant fraction of the rat prostate. The receptor has a particular binding specificity towards 5αdihydrotestosterone. Testosterone is bound to a lesser extent but other steroids, including certain androgenic hormones, are not bound. The sedimentation coefficient of 8·0 s and the frictional ratio of 1·96, equivalent to a molecular weight of 2·74 × 105, clearly distinguish the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
3

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(64 citation statements)
references
References 0 publications
4
57
0
3
Order By: Relevance
“…As all prostatic rat steroid 5a-R E D activity is reportedly located in the nucleus [ 18-203, one can hypothesize that the type I isozyme could therefore be active when T accumulates in the nucleus,, e.g. due to binding to the androgen receptor [21,22]. As the V maJ K m ratio of the type I isozyme still contributes substantially to the total potential in vivo 5 a-R E D activity, an anabolic function for this subtype in rat prostate is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…As all prostatic rat steroid 5a-R E D activity is reportedly located in the nucleus [ 18-203, one can hypothesize that the type I isozyme could therefore be active when T accumulates in the nucleus,, e.g. due to binding to the androgen receptor [21,22]. As the V maJ K m ratio of the type I isozyme still contributes substantially to the total potential in vivo 5 a-R E D activity, an anabolic function for this subtype in rat prostate is plausible.…”
Section: Discussionmentioning
confidence: 99%
“…In the late 1960s, the androgen receptor was discovered and characterized by three independent groups -those of S. Liao, N. Bruchovsky and I. Mainwaring [26][27][28] . Screening of chemical libraries for androgen-receptor blockers led to the discovery of cyproterone -a 'pure' steroidal anti-androgen that competitively inhibits the binding of dihydrotestosterone (DHT) or testosterone to the androgen receptor 29 …”
Section: Boxmentioning
confidence: 99%
“…As these new agents were being developed, it became clear that none of these approaches (orchiectomy, LHRH agonists or anti-androgens) were by themselves able to cure patients with advanced prostate cancer 28 . The next logical step, therefore, was to combine androgenablative therapy directed at both reducing the amount of testosterone released from the testes (orchiectomy or LHRH agonist) and at neutralizing androgens produced by the adrenal glands with anti-androgens that act directly within prostate cancer cells.…”
Section: Boxmentioning
confidence: 99%
“…To test the generality of this concept, we determined whether the specific receptors for [3H]DHT and [3H]estradiol would enhance binding to their respective target-tissue chromatins. Previous investigators have reported the in vivo (22) and in vitro (3) association of estradiol and the in vivo association of DHT with target-tissue chromatins (14). No evidence was presented to show whether the chromatins remained intact during the experimental procedures, or whether the target-cell receptor might have been adsorbed to the extracted chromatin.…”
mentioning
confidence: 98%